Lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres and preparation method and application thereof

By using lanthanum oxide-doped nickel cobalt acid/carbon porous hollow microspheres in the negative electrode material of lithium-ion battery, the problems of reduced specific capacity and poor stability caused by large volume changes in the prior art are solved, and high cycle stability is achieved and increase in reversible capacitance.

CN119008904BActive Publication Date: 2025-02-07LUDONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411141873.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-07
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The volume of the existing lithium-ion battery anode material changes greatly during charging and discharging, resulting in a decrease in specific capacity and poor stability, making it difficult to meet the needs of high-performance electric vehicles and hybrid vehicles.

Method used

The nickel cobalt acid/carbon porous hollow microspheres doped with lanthanum oxide are prepared by solvothermal reaction and calcining steps, and the grain size of nickel cobalt acid is reduced by porous lanthanum oxide nanoparticles, and the volume changes are buffered by the coated carbon network.

Benefits of technology

It significantly improves the electrochemical performance of the negative electrode, enhances cycling stability and reversible capacitance, effectively suppresses volume expansion and particle aggregation, and improves the conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008904B_ABST
    Figure CN119008904B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion battery materials, and in particular to a lanthanum oxide doped nickel cobaltate / carbon porous hollow microsphere and a preparation method and application thereof. The nickel cobaltate / carbon porous hollow microsphere is prepared by a solvent thermal reaction of a divalent nickel salt, a divalent cobalt salt and isophthalic acid, and further hydrothermally reacted with lanthanum oxide and calcined in an inert gas atmosphere to obtain lanthanum oxide doped nickel cobaltate / carbon porous hollow microsphere. The doping of porous lanthanum oxide nanoparticles is beneficial to reducing the grain size and electrode internal resistance of nickel cobaltate and improving the ion and electron transmission efficiency. The hollow porous microspheres coated with a carbon network have good mechanical strength, effectively inhibit volume expansion and particle aggregation during charging and discharging, and improve the conductivity of the composite material. The nanostructure of the composite microsphere can provide abundant active sites for the rapid redox reaction of metal ions, thereby effectively improving the specific capacity. The material exhibits excellent lithium storage performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lanthanum oxide-doped nickel cobaltate / carbon porous hollow microsphere and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in mobile communication devices, portable electronic devices, and electric / hybrid vehicles due to their high energy density and long cycle life. Currently, commercial graphite anode materials have a low theoretical capacity (372 mAh g -1 ) cannot meet the growing demand for high-performance electric vehicles and hybrid vehicles. Therefore, it is urgent to develop new negative electrode materials with high specific capacity. Transition metal oxides are considered to be a promising high energy storage (>600mAh g -1 ) anode materials. However, the rapid volume change during the charge / discharge process leads to a decrease in specific capacity and poor stability, limiting its commercial application in lithium-ion batteries.

[0003] An effective strategy to solve the above problems is to combine transition metal oxides with flexible carbon matrices, which can not only alleviate the volume change but also improve the electronic conductivity of the composite material. On the other hand, binary transition metal oxides combine the advantages of two different metals and show more outstanding application prospects. Spinel phase nickel cobalt oxide has a high theoretical capacity (891 mAh g -1 ) and low cost make it an ideal candidate material for the next generation of negative electrodes. Compared with single nickel oxide or cobalt oxide, nickel cobalt oxide has higher stability, electrochemical activity and lithium storage performance. However, due to the volume expansion and inherent semiconductor properties of nickel cobalt oxide during the charge and discharge process, its cycle life and rate performance are difficult to meet commercial requirements. Summary of the invention

[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a lanthanum oxide-doped nickel cobaltate / carbon porous hollow microsphere and a preparation method and application thereof.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] The first aspect of the present invention is to provide a method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres, comprising the following steps:

[0007] (1) preparing nickel cobaltate / carbon porous hollow microspheres: dissolving 5 to 8 parts of divalent nickel salt, 10 to 16 parts of divalent cobalt salt and 8 to 12 parts of isophthalic acid in a solvent 1 by weight, stirring, and then transferring to a reaction kettle for solvothermal reaction at 120 to 180° C., then cooling to room temperature, and calcining at 300 to 360° C. in an air atmosphere to obtain the nickel cobaltate / carbon porous hollow microspheres;

[0008] (2) Preparation of lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres: 2 to 5 parts by weight of the nickel cobaltate / carbon porous hollow microspheres obtained in step (1) and 0.2 to 2.5 parts of lanthanum oxide powder are added to solvent 2, uniformly dispersed and then transferred to a reaction kettle for solvent thermal treatment at 120 to 180° C., cooled, washed and dried, and calcined at 300 to 600° C. in an inert atmosphere to obtain lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres.

[0009] The lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres prepared by the preparation method of the lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres provided by the present invention have the following beneficial effects:

[0010] The doping of porous lanthanum oxide nanoparticles is beneficial to reducing the grain size and electrode internal resistance of nickel cobalt oxide. The nickel cobalt oxide crystals are uniform in size and have good reversibility, which is beneficial to improving the ion and electron transmission efficiency, thereby significantly improving the electrochemical performance of the negative electrode.

[0011] The hollow porous microspheres coated with carbon networks have good mechanical strength, which can effectively inhibit volume expansion and particle aggregation during charge and discharge, while improving the conductivity of the composite material;

[0012] The nanostructure of the composite microspheres can provide abundant active sites for the rapid redox reaction of metal ions, thereby effectively improving the specific capacity.

[0013] On the basis of the above technical solution, the present invention can also make the following technical improvements:

[0014] Furthermore, in parts by weight, the first solvent includes 60 to 150 parts of acetone and 60 to 150 parts of N,N-dimethylformamide, and the second solvent includes 70 to 120 parts of deionized water and 70 to 120 parts of ethanol.

[0015] Furthermore, in step (1), stirring is performed for 4 to 8 hours, preferably 5 hours.

[0016] Furthermore, in step (1), the divalent nickel salt is selected from any one or more of nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel sulfate and its hydrate, and nickel acetate and its hydrate, and the divalent cobalt salt is selected from any one or more of cobalt nitrate and its hydrate, cobalt chloride and its hydrate, cobalt sulfate and its hydrate, and cobalt acetate and its hydrate.

[0017] Furthermore, in step (1), the solvent thermal reaction time is 2 to 6 hours, and the calcination time is 0.5 to 2 hours.

[0018] Furthermore, in step (2), the solvent thermal treatment time is 12 to 24 hours, and the calcination time is 0.5 to 3 hours.

[0019] The second aspect of the present invention is to provide a lanthanum oxide doped nickel cobaltate / carbon porous hollow microsphere, which is prepared by the preparation method of the lanthanum oxide doped nickel cobaltate / carbon porous hollow microsphere.

[0020] Another aspect of the present invention is to provide the use of the above-mentioned lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres in lithium ion battery negative electrode materials.

[0021] Compared with the prior art, the present invention has the following technical effects:

[0022] The preparation method provided by the present invention fully utilizes the advantages of porous lanthanum oxide nanoparticles in reducing the grain size of nickel cobalt oxide and improving the ion and electron transmission efficiency, combines the advantages of large specific surface area, good conductivity, and stable chemical properties of the coated carbon network and the unique hollow porous structure of porous hollow microspheres to buffer the volume change of the electrode material, and prepares a lithium ion battery negative electrode material with excellent cycle performance and high reversible capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope photograph of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 1;

[0024] Figure 2 is the X-ray diffraction pattern of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 1;

[0025] Figure 3 The nitrogen adsorption-desorption isotherm and pore size distribution of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 1;

[0026] Figure 4 is the cycle performance curve of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 1;

[0027] Figure 5is the cycle performance curve of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 2;

[0028] Figure 6 is the cycle performance curve of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres prepared in Example 3;

[0029] Figure 7 This is a cycle performance curve of nickel cobaltate / carbon porous hollow microspheres not doped with lanthanum oxide prepared in Comparative Example 1;

[0030] Figure 8 This is the cycle performance curve of the nickel cobaltate / carbon porous hollow microspheres doped with excess lanthanum oxide prepared in Comparative Example 2. DETAILED DESCRIPTION

[0031] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0032] Example 1

[0033] (1) dissolving 6 parts of nickel nitrate hexahydrate, 12 parts of cobalt nitrate hexahydrate and 10 parts of isophthalic acid in a mixed solvent of 100 parts of acetone and 100 parts of N,N-dimethylformamide by weight, stirring for 5 hours, transferring to a reaction kettle for solvothermal reaction at 160° C. for 4 hours, cooling to room temperature, and calcining the obtained brown powder in air at 350° C. for 1 hour to obtain nickel cobaltate / carbon porous hollow microspheres;

[0034] (2) By weight, 3 parts of nickel cobaltate / carbon porous hollow microspheres and 1 part of lanthanum oxide powder were added to a mixed solvent of 100 parts of deionized water and 100 parts of ethanol, and ultrasonically dispersed uniformly. The mixture was transferred to a reactor and subjected to solvent thermal treatment at 160° C. for 20 hours. After cooling, the mixture was washed and dried, and calcined at 350° C. for 1 hour under an inert atmosphere to obtain lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres.

[0035] Example 2

[0036] (1) dissolving 5 parts of nickel chloride hexahydrate, 10 parts of cobalt chloride hexahydrate and 8 parts of isophthalic acid in a mixed solvent of 60 parts of acetone and 60 parts of N,N-dimethylformamide by weight, stirring for 5 hours, transferring to a reaction kettle for solvothermal reaction at 140° C. for 6 hours, cooling to room temperature, and calcining the obtained brown powder in air at 330° C. for 2 hours to obtain nickel cobaltate / carbon porous hollow microspheres;

[0037] (2) By weight, 3 parts of nickel cobaltate / carbon porous hollow microspheres and 0.3 parts of lanthanum oxide powder were added to a mixed solvent of 70 parts of deionized water and 70 parts of ethanol, and ultrasonically dispersed uniformly. The mixture was transferred to a reactor and subjected to solvent thermal treatment at 140° C. for 24 hours. After cooling, the mixture was washed and dried, and calcined at 500° C. for 2 hours under an inert atmosphere to obtain lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres.

[0038] Example 3

[0039] (1) dissolving 8 parts of nickel sulfate, 16 parts of cobalt sulfate and 12 parts of isophthalic acid in a mixed solvent of 150 parts of acetone and 150 parts of N,N-dimethylformamide by weight, stirring for 5 hours, transferring to a reaction kettle for solvothermal reaction at 180° C. for 5 hours, cooling to room temperature, and calcining the obtained brown powder at 360° C. in air for 1.5 hours to obtain nickel cobaltate / carbon porous hollow microspheres;

[0040] (2) By weight, 5 parts of nickel cobalt oxide / carbon porous hollow microspheres and 2.5 parts of lanthanum oxide powder were added to a mixed solvent of 120 parts of deionized water and 120 parts of ethanol, and ultrasonically dispersed uniformly. The microspheres were transferred to a reactor and subjected to solvent thermal treatment at 180° C. for 16 hours. After cooling, the microspheres were washed and dried, and calcined at 450° C. for 2 hours under an inert atmosphere to obtain lanthanum oxide-doped nickel cobalt oxide / carbon porous hollow microspheres.

[0041] Comparative Example 1

[0042] By weight, 6 parts of nickel nitrate hexahydrate, 12 parts of cobalt nitrate hexahydrate and 10 parts of isophthalic acid were dissolved in a mixed solvent of 100 parts of acetone and 100 parts of N,N-dimethylformamide, and after stirring for 5 hours, the mixture was transferred to a reactor and subjected to a solvent thermal reaction at 160° C. for 4 hours. The mixture was cooled to room temperature, and the obtained brown powder was calcined in air at 350° C. for 1 hour to obtain nickel cobaltate / carbon porous hollow microspheres not doped with lanthanum oxide.

[0043] Comparative Example 2

[0044] (1) By weight, 6 parts of nickel nitrate hexahydrate, 12 parts of cobalt nitrate hexahydrate and 10 parts of isophthalic acid were dissolved in a mixed solvent of 100 parts of acetone and 100 parts of N,N-dimethylformamide, stirred for 5 hours, transferred to a reactor and subjected to a solvothermal reaction at 160° C. for 4 hours, cooled to room temperature, and the obtained brown powder was calcined in air at 350° C. for 1 hour to obtain nickel cobaltate / carbon porous hollow microspheres of lanthanum oxide.

[0045] (2) By weight, 3 parts of nickel cobaltate / carbon porous hollow microspheres and 3 parts of lanthanum oxide powder were added to a mixed solvent of 100 parts of deionized water and 100 parts of ethanol, and ultrasonically dispersed uniformly. The mixture was transferred to a reactor and subjected to solvent thermal treatment at 160° C. for 20 hours. After cooling, the mixture was washed and dried, and calcined at 350° C. for 1 hour under an inert atmosphere to obtain nickel cobaltate / carbon porous hollow microspheres doped with excess lanthanum oxide.

[0046] In order to verify the structural characteristics and performance of the product obtained by the method of the present invention, the lanthanum oxide doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 1 were characterized and tested. The scanning electron microscopy of the lanthanum oxide doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 1 is as follows: Figure 1 The X-ray diffraction pattern is shown in Figure 2 As shown, the nitrogen adsorption-desorption isotherm and pore size distribution are shown in Figure 3 As shown, the cycle performance curve is as follows Figure 4 The cycle performance curve of the lanthanum oxide doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 2 is shown in Figure 5 The cycle performance curve of the lanthanum oxide doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 3 is shown in Figure 6 The cycle performance curve of nickel cobalt oxide / carbon porous hollow microspheres without lanthanum oxide obtained in Comparative Example 1 is shown in Figure 7 The cycle performance curve of the nickel cobalt oxide / carbon porous hollow microspheres doped with excess lanthanum oxide obtained in Comparative Example 2 is shown in Figure 8 shown.

[0047] from Figure 1 It can be seen that the surface of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres obtained in Example 1 is composed of a large number of nanoparticles and is relatively rough, which can effectively increase the active sites, thereby accelerating the electrochemical reaction kinetics. The hollow morphology can be seen through the broken microspheres.

[0048] from Figure 2It can be seen that the lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres obtained in Example 1 are located at 18.93 °, 31.15 °, 36.70 °, 38.48 °, 44.63 °, 55.60 °, 59.11 °, 65.13 ° and 77.1 °. The diffraction peaks are relatively sharp, which are consistent with the crystal plane of the nickel cobaltate with a spinel structure; in addition to nickel cobaltate, a nickel metal element is also formed, and nickel can react with lithium oxide to improve the conductivity of the negative electrode. In addition, the presence of lanthanum oxide can also be clearly seen. Compared with nickel cobaltate, the diffraction peaks of the material doped with lanthanum oxide move slightly to a smaller angle. This is caused by the lattice expansion of nickel cobaltate caused by lanthanum oxide doping, indicating that lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres have been successfully prepared.

[0049] from Figure 3 It can be seen that the nitrogen adsorption-desorption isotherm of the lanthanum oxide-doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 1 conforms to the IV adsorption type, indicating that the material has a mesoporous structure with a pore size concentrated at 4 nm. The specific surface area of ​​the material calculated by BET is 67.94 m 2 / g, a higher specific surface area can expand the contact area between the electrolyte and the electrode material and increase the transmission rate of lithium ions.

[0050] from Figure 4 It can be seen that the lanthanum oxide-doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 1 have a -1 After 1000 cycles at the same current density, the specific capacity can reach 915.8 mAh g -1 , indicating that the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres obtained in Example 1 have higher reversible capacitance and better cycle stability.

[0051] from Figure 5 It can be seen that at 1Ag -1 After 1000 cycles at the current density, the specific capacity of the lanthanum oxide-doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 2 was 686.2 mAh g -1 , indicating that the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres obtained in Example 2 have higher reversible capacitance and better cycle stability.

[0052] from Figure 6 It can be seen that at 1Ag -1 After 1000 cycles at the current density, the specific capacity of the lanthanum oxide-doped nickel cobalt oxide / carbon porous hollow microspheres obtained in Example 3 was 674.8 mAh g -1 , indicating that the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres obtained in Example 3 have higher reversible capacitance and better cycle stability.

[0053] from Figure 7 It can be seen that at 1Ag-1 After 1000 cycles at the current density, the specific capacity of the nickel cobalt oxide / carbon porous hollow microspheres without lanthanum oxide obtained in Comparative Example 1 was only 56.7 mAh g -1 , indicating that the reversible capacity and cycle stability of nickel cobalt oxide / carbon porous hollow microspheres without lanthanum oxide doping are poor.

[0054] from Figure 8 It can be seen that at 1Ag -1 After 1000 cycles at the current density, the specific capacity of the nickel cobalt oxide / carbon porous hollow microspheres doped with excess lanthanum oxide obtained in Comparative Example 2 was only 269.2 mAh g -1 , indicating that the reversible capacity and cycle stability of nickel cobalt oxide / carbon porous hollow microspheres doped with excess lanthanum oxide are poor.

[0055] The preferred embodiments of the present invention described above are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres, characterized in that: The following steps are involved: (1) preparing nickel cobaltate / carbon porous hollow microspheres: dissolving 5 to 8 parts of divalent nickel salt, 10 to 16 parts of divalent cobalt salt and 8 to 12 parts of isophthalic acid in a solvent 1 by weight, stirring, and then transferring to a reaction kettle for solvothermal reaction at 120 to 180° C., then cooling to room temperature, and calcining at 300 to 360° C. in an air atmosphere to obtain the nickel cobaltate / carbon porous hollow microspheres; (2) Preparation of lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres: 2 to 5 parts by weight of the nickel cobaltate / carbon porous hollow microspheres obtained in step (1) and 0.2 to 2.5 parts of lanthanum oxide powder are added to solvent 2, uniformly dispersed and then transferred to a reaction kettle for solvent thermal treatment at 120 to 180° C., cooled, washed and dried, and calcined at 300 to 600° C. in an inert atmosphere to obtain lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres.

2. The method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 1, characterized in that: In parts by weight, the first solvent comprises 60 to 150 parts of acetone and 60 to 150 parts of N,N-dimethylformamide, and the second solvent comprises 70 to 120 parts of deionized water and 70 to 120 parts of ethanol.

3. The method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 1, characterized in that: In step (1), stirring is performed for 4 to 8 hours.

4. The method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 3, characterized in that: In step (1), stirring is performed for 5 hours.

5. The method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 1, characterized in that: In step (1), the divalent nickel salt is selected from any one or more of nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel sulfate and its hydrate, and nickel acetate and its hydrate, and the divalent cobalt salt is selected from any one or more of cobalt nitrate and its hydrate, cobalt chloride and its hydrate, cobalt sulfate and its hydrate, and cobalt acetate and its hydrate.

6. The method for preparing lanthanum oxide doped nickel cobaltate / carbon porous hollow microspheres according to claim 1, characterized in that: In step (1), the solvent thermal reaction time is 2 to 6 hours, and the calcination time is 0.5 to 2 hours.

7. The method for preparing lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 1, characterized in that: In step (2), the solvent thermal treatment time is 12 to 24 hours, and the calcination time is 0.5 to 3 hours.

8. A lanthanum oxide-doped nickel cobaltate / carbon porous hollow microsphere, characterized in that: The lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres are prepared by the preparation method of any one of claims 1 to 7.

9. Use of the lanthanum oxide-doped nickel cobaltate / carbon porous hollow microspheres according to claim 8 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of lanthanum ferrum nickel doped lithium cobaltate-carbon composite positive electrode material

    CN103794785A

  • Preparation method of rubidium doped nickel cobaltite negative electrode material

    CN110336013A